Matte anti-slip, anti-fouling and easy-to-clean marble tile and preparation method thereof
By adopting a three-layer wax water coating method on marble tiles, the problems of poor anti-graffiti performance and dust accumulation of matte marble tiles are solved, and the effect of enhancing anti-slip and anti-fouling performance is achieved to ensure the gloss of the brick surface and aesthetics.
Patent Information
- Application Number
- CN202310811449.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-07-03
AI Technical Summary
The existing matte marble tiles have shortcomings in terms of poor graffiti resistance and dust accumulation, and it is difficult to take into account both anti-slip and anti-fouling properties.
The preparation method of a three-layer structure is adopted, including a primer, an intermediate layer and a topcoat. The surface structure with toughness and scattering properties are formed by coating with specific formulas, which enhances the anti-slip and anti-fouling properties of the brick surface. The base coat consists of water, nano-silica dispersion and white carbon black, the intermediate layer contains solvent, silicone resin and silane coupling agent, the top coat contains silicon source, silicone and acetic acid, and is treated with ultra-clean and brightness. Insulation annealing.
It realizes that matte marble tiles maintain a certain gloss while improving anti-slip and anti-fouling performance. The static friction coefficient can increase after trampling, and pollutants can be rinsed clean with water to meet the level 5 stain resistance standard.
Smart Images

Figure CN116947534B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of marble tiles, and in particular to a matte anti-skid, anti-fouling and easy-to-clean marble tile and a preparation method thereof. Background Art
[0002] In recent years, as the decoration style has changed from the past magnificent to the present deep low-key, luxurious but not flashy, the mainstream trend of ceramic products has gradually tended to the plain matte, plain concave and convex texture, a large category of plain and matte products. It has the characteristics of non-glare and no reflection imaging, which is more in line with the aesthetic needs of today's customers. At the same time, this type of brick is also labeled as hiding dirt, hiding dust, and difficult to clean. During the sintering process of ceramic tiles, the surface glaze will form a micro-continuous peak and valley structure, which can cause light scattering, and the depressions are also prone to dirt accumulation and difficult to clean. There are roughly two types of matte bricks on the market. One is that after sintering, it is lightly polished and softly polished to reduce the drop of the peak and valley structure, and a matte brick with a gloss of about 10° is prepared; the other is sintered into a matte brick with a gloss of about 10° and a warm feel through a special glaze (gold velvet, matte glaze, candy glaze, skin glaze, etc.).
[0003] However, the above matte tiles all have poor anti-graffiti performance and can hide dirt and dust. To this end, we provide a matte anti-slip, anti-fouling and easy-to-clean marble tile and a preparation method thereof. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the present invention provides a matte anti-slip, anti-fouling and easy-to-clean marble tile and a preparation method thereof. During the preparation process, wax water with good toughness is coated on the surface of the marble tile, which can reduce the difference between peaks and valleys but will not completely fill the peak-valley structure, thereby increasing the glossiness of the marble tile surface and maintaining a certain anti-slip performance. Even if the pits on the surface are too shallow, the anti-fouling performance requirements can be met.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] The first object of the present application is to provide a matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a base coating, an intermediate layer and a top coating sequentially coated on the semi-finished ceramic tile;
[0007] The base coating wax water for forming the base coating layer comprises the following raw materials in parts by weight:
[0008] Water: 80-95 parts
[0009] Nano-silicon dioxide dispersion: 15-20 parts
[0010] The nano silicon dioxide dispersion comprises the following raw materials in parts by weight:
[0011] White carbon black: 2-5 parts
[0012] Ethanol: 13-15 parts;
[0013] White carbon black is one or more of R106, R380 and R200;
[0014] The intermediate wax water forming the intermediate layer includes the following raw materials in parts by weight:
[0015] Solvent: 50-60 parts
[0016] Silicone resin: 36-45 parts
[0017] Silane coupling agent: 1-5 parts
[0018] Curing agent: 12-15 parts
[0019] Catalyst: 0.1-1 part;
[0020] The solvent is one or more of ethanol, n-butanol, propylene glycol methyl ether, glycerol, and dimethyl nylonate;
[0021] The surface coating wax water for forming the surface coating comprises the following raw materials in parts by weight:
[0022] Silicon source: 5-15 parts
[0023] Silicone: 5-10 parts
[0024] Ethanol: 70-90 parts
[0025] Water: 1-5 parts
[0026] Acetic acid: 0.02-0.1 parts
[0027] Pore former: 0.5-1 part.
[0028] Furthermore, in the raw materials of the intermediate wax water, the silicone resin is one or more of SJ909N, SJ909P, SJ509P, and S0234.
[0029] Furthermore, in the raw material of the intermediate wax water, the silane coupling agent is one or more of KH-560, KH550, and KH792.
[0030] Furthermore, in the raw material of the intermediate wax water, the curing agent is one or more of N-aminoethylpiperazine, DETA, diaminodiphenylmethane, methyltributylacetonato oxime silane, and vinyltributylacetonato oxime silane.
[0031] Furthermore, in the raw material of the intermediate wax water, the catalyst is one or more of dibutyltin dilaurate, dibutyltin diacetate, and tetrabutyl titanate.
[0032] Furthermore, in the surface coating wax water, the silicon source is one or two of TEOS and tetramethoxysilane.
[0033] Furthermore, in the surface coating wax water, the organosilicon is one or two of octyltriethoxysilane and MTEOS.
[0034] Furthermore, in the surface wax water, the pore-forming agent is F127.
[0035] The second object of the present invention is to provide a method for preparing the above-mentioned matte anti-slip, anti-fouling and easy-to-clean marble tiles, comprising the following steps:
[0036] S1. Preparation of base wax water:
[0037] Prepare materials according to the weight composition of each raw material in the base coating wax water, and fully mix the raw materials to obtain the base coating wax water;
[0038] S2. Preparation of intermediate wax water:
[0039] Prepare materials according to the weight composition of each raw material in the intermediate wax water, and fully mix each raw material to obtain the base coating wax water;
[0040] S3. Preparation of surface wax water:
[0041] Prepare materials according to the weight composition of each raw material in the surface wax water, and fully mix the raw materials to obtain the surface wax water;
[0042] S4 semi-finished ceramic tiles for the first ultra-clean and bright treatment; dripping the primer wax water, the primer wax water cast on the surface of the ceramic tile, to obtain a semi-finished ceramic tile having a primer coating;
[0043] S5. The semi-finished ceramic tile having a primer layer is subjected to a second ultra-clean and bright treatment; dripping intermediate wax water, the intermediate wax water is applied to the primer layer of the tile, and the semi-finished ceramic tile having an intermediate layer is provided;
[0044] S6. Applying the surface wax water to the bottom coating of the semi-finished ceramic tile with the middle layer, and subjecting it to heat preservation annealing treatment, a matte anti-skid, anti-fouling and easy-to-clean ceramic tile is obtained.
[0045] Furthermore, the first super-brightening treatment and the second super-brightening treatment are performed using a super-brightening machine.
[0046] Furthermore, when the first super-bright treatment is performed using a super-bright machine, the super-bright machine is set to perform super-bright treatment with 12 groups of hard fiber grinding heads + 8 groups of sponge grinding heads.
[0047] Furthermore, when the second super-bright treatment is performed using a super-bright machine, the super-bright machine is set to use 10 groups of sponge grinding heads for super-bright treatment.
[0048] Furthermore, in step S6, the heat preservation annealing treatment is carried out by heat preservation annealing at 400° C. for 10-15 minutes.
[0049] The beneficial effects of the present invention are:
[0050] 1. The preparation method described in the present application is to first use a primer wax water to form a base coat, superimpose a tough middle layer, and then superimpose a top coat with good scattering properties and good hydrophilicity. The prepared ceramic tile has a matte finish and well-balanced anti-fouling and anti-slip properties.
[0051] 2. The ceramic tiles described in this application have the advantages of being matte, non-slip, anti-fouling and easy to clean. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0053] Figure 1 This is a schematic diagram of the contour of the 3D fitting image of the matte anti-slip, anti-fouling and easy-to-clean marble tile described in Example 6 of the present application under a microscope at 500 times magnification;
[0054] Figure 2 This is a schematic diagram of the contour of the 3D fitting image of the matte anti-slip, anti-fouling and easy-to-clean marble tile described in Example 6 of the present application after a stepping test under a microscope at 500 times magnification;
[0055] Figure 3 This is a schematic diagram of the contour of the 3D fitting image of the marble tile described in Comparative Example 1 of the present application under a microscope at 500 times magnification.
[0056] Figure 4 This is a schematic diagram of the contour of the 3D fitting image of the marble tile described in Comparative Example 2 of the present application under a microscope at 500 times magnification;
[0057] Figure 5 This is a schematic diagram of the contour of the 3D fitting image of the marble tile described in Comparative Example 3 of the present application under a microscope at 500 times magnification. DETAILED DESCRIPTION
[0058] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0059] In the actual development and production of ceramic tiles, we found that through observation under a microscope, the poor anti-fouling performance of matte tiles is mainly due to the presence of micron-level pores and microscopic continuous peak-valley structures on the glaze surface. On the market, similar methods have been used to develop some matte anti-fouling wax water to fill the pores and peak-valley structures on the brick surface to improve its anti-fouling performance. However, once the peak-valley structure of the brick surface is filled, its surface roughness decreases, resulting in a small static friction coefficient on the brick surface and reduced anti-slip performance.
[0060] To this end, we have developed a new type of primer wax water and intermediate wax water. By applying the primer wax water and intermediate wax water to the semi-finished ceramic tiles in sequence, the surface of the finished ceramic tiles can reduce the difference between the peaks and valleys but will not completely fill the peak-valley structure, so that the glossiness of the tile surface is increased and a certain anti-slip performance is maintained. At the same time, the pits on the surface are too shallow to meet the anti-fouling performance requirements. Moreover, after the finished ceramic tiles are continuously stepped on, the static friction coefficient of the tile surface increases. Analysis shows that the primer wax water has a certain flexibility and plastic deformation after film formation, and the difference between the peak-valley structure is increased under the action of external force, so that the anti-slip performance is improved. However, the anti-fouling performance of the sample tiles that have been stepped on does not meet the standards. Therefore, on this basis, a surface wax water is further developed to solve the problems of increased glossiness and dirt sticking. At the same time, we found that using the matte anti-fouling wax on the market as the top coating wax will have durability problems, and when the height difference of the peak-to-valley structure reaches 10um, visible dirt will be stuck, and it cannot be cleaned with water. The hydrophobicity of the surface prevents water from infiltrating the pits on the brick surface and cannot remove the dirt in the pits. For this reason, we have developed a new type of primer wax, middle wax, and top coating wax. When the top coating wax is superimposed on the middle layer, it has the effect of reducing gloss and facilitating cleaning;
[0061] After coating the finished ceramic tiles with the primer layer formed by the primer wax water, the middle layer formed by the intermediate wax water, and the top layer formed by the top wax water described in this application, a stepping test is carried out. The stepped-on samples are then tested for pollution resistance according to the national standard "GB / T3810.14-2016" for pollution resistance of ceramic tiles. The pollutants can be directly rinsed off with water to meet the level 5 pollution resistance standard.
[0062] In addition, the adhesion and superposition of the base coat, the middle coat, and the top coat make the finished ceramic tile have both anti-fouling and anti-slip properties, but there is a problem of unstable glossiness of the tile surface, which affects the aesthetic appearance. After analysis, it was found that the base coat wax water did not fill the micron-level pores sufficiently and the wax water was not evenly polished. Therefore, we adjusted the preparation method of ceramic tiles, and used polishing to apply the base coat wax water to the bottom layer of the tile surface, and stabilized the glossiness at about 30°. The 30° glossiness exceeds the effect of the middle wax water on the glossiness, avoiding the middle wax water from affecting the appearance of the tile surface; then the middle wax water with good plastic deformation is applied as the middle layer on the tile surface, and finally the top coat wax water with good scattering and hydrophilicity is applied as the top coat on the top layer, to obtain matte ceramic tiles with good appearance transparency, good anti-fouling and good anti-slip properties.
[0063] To this end, we provide a matte anti-slip, anti-fouling and easy-to-clean marble tile and a preparation method thereof.
[0064] Example 1
[0065] A wax water composition, comprising a base coating wax water, an intermediate wax water, and a surface coating wax water;
[0066] The base coating wax water comprises the following raw materials in parts by weight:
[0067] Water: 80 parts
[0068] Nano-silicon dioxide dispersion: 15 parts;
[0069] The nano silicon dioxide dispersion comprises the following raw materials in parts by weight:
[0070] White carbon black: R106 2 parts
[0071] Ethanol: 13 parts;
[0072] The preparation method of the primer wax water comprises preparing materials according to the weight composition of each raw material in the primer wax water, and fully mixing each raw material to obtain the primer wax water;
[0073] The intermediate wax water comprises the following raw materials in parts by weight:
[0074] Solvent: 50 parts ethanol
[0075] Silicone resin: SJ909N 36 parts
[0076] Silane coupling agent: KH-560 1 part
[0077] Curing agent: 12 parts N-aminoethylpiperazine
[0078] Catalyst: 0.1 part of dibutyltin dilaurate;
[0079] The preparation method of the intermediate wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the intermediate wax water, and fully mixing the various raw materials to obtain the intermediate wax water.
[0080] The surface wax water comprises the following raw materials in parts by weight:
[0081] Silicon source: TEOS, 5 parts of tetramethoxysilane
[0082] Silicone: Octyltriethoxysilane, MTEOS 5 parts
[0083] Ethanol: 70 parts
[0084] Water: 1 part
[0085] Acetic acid: 0.02 parts
[0086] Pore former: F127 0.5 parts.
[0087] The preparation method of the surface coating wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the surface coating wax water, and fully mixing the various raw materials to obtain the surface coating wax water.
[0088] Example 2
[0089] A wax water composition, comprising a base coating wax water, an intermediate wax water, and a surface coating wax water;
[0090] The base coating wax water comprises the following raw materials in parts by weight:
[0091] Water: 95 parts
[0092] Nano-silicon dioxide dispersion: 20 parts
[0093] The nano silicon dioxide dispersion comprises the following raw materials in parts by weight:
[0094] White carbon black: 5 parts
[0095] Ethanol: 15 parts;
[0096] White carbon black is R380;
[0097] The preparation method of the primer wax water comprises preparing materials according to the weight composition of each raw material in the primer wax water, and fully mixing each raw material to obtain the primer wax water;
[0098] The intermediate wax water comprises the following raw materials in parts by weight:
[0099] Solvent: 60 parts of n-butanol
[0100] Silicone resin: SJ909P 45 parts
[0101] Silane coupling agent: KH550 5 parts
[0102] Curing agent: 15 parts of diaminodiphenylmethane
[0103] Catalyst: 1 part of dibutyltin diacetate;
[0104] The preparation method of the intermediate wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the intermediate wax water, and fully mixing the various raw materials to obtain the intermediate wax water.
[0105] The surface wax water comprises the following raw materials in parts by weight:
[0106] Silicon source: TEOS, 15 parts of tetramethoxysilane
[0107] Silicone: MTEOS 10 parts
[0108] Ethanol: 90 parts
[0109] Water: 5 parts
[0110] Acetic acid: 0.1 parts
[0111] Pore former: 1 part of F127.
[0112] The preparation method of the surface coating wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the surface coating wax water, and fully mixing the various raw materials to obtain the surface coating wax water.
[0113] Example 3
[0114] A wax water composition, comprising a base coating wax water, an intermediate wax water, and a surface coating wax water;
[0115] The base coating wax water comprises the following raw materials in parts by weight:
[0116] Water: 75 parts
[0117] Nano-silicon dioxide dispersion: 18 parts
[0118] The nano silicon dioxide dispersion comprises the following raw materials in parts by weight:
[0119] White carbon black: 3 parts
[0120] Ethanol: 15 parts;
[0121] White carbon black is R200;
[0122] The preparation method of the primer wax water comprises preparing materials according to the weight composition of each raw material in the primer wax water, and fully mixing each raw material to obtain the primer wax water;
[0123] The intermediate wax water comprises the following raw materials in parts by weight:
[0124] Solvent: 55 parts of propylene glycol methyl ether
[0125] Silicone resin: SJ509P 40 parts
[0126] Silane coupling agent: KH792 4 parts
[0127] Curing agent: DETA 13 parts
[0128] Catalyst: 0.5 parts;
[0129] The preparation method of the intermediate wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the intermediate wax water, and fully mixing the various raw materials to obtain the intermediate wax water.
[0130] The surface wax water comprises the following raw materials in parts by weight:
[0131] Silicon source: 10 parts of tetramethoxysilane
[0132] Silicone: MTEOS 8 parts
[0133] Ethanol: 80 parts
[0134] Water: 3 parts
[0135] Acetic acid: 0.06 parts
[0136] Pore former: F127 0.8 parts.
[0137] Example 4
[0138] A wax water composition, comprising a base coating wax water, an intermediate wax water, and a surface coating wax water;
[0139] The base coating wax water comprises the following raw materials in parts by weight:
[0140] Water: 95 parts
[0141] Nano-silicon dioxide dispersion: 16 parts
[0142] The nano silicon dioxide dispersion comprises the following raw materials in parts by weight:
[0143] White carbon black: 1 part of R106, 1 part of R380, 1 part of R200;
[0144] Ethanol: 13 parts;
[0145] The preparation method of the primer wax water comprises preparing materials according to the weight composition of each raw material in the primer wax water, and fully mixing each raw material to obtain the primer wax water;
[0146] The intermediate wax water comprises the following raw materials in parts by weight:
[0147] Solvent: 60 parts of glycerol
[0148] Silicone resin: S0234 36 parts
[0149] Silane coupling agent: KH792 5 parts
[0150] Curing agent: 12 parts N-aminoethylpiperazine
[0151] Catalyst: 0.3 parts;
[0152] The preparation method of the intermediate wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the intermediate wax water, and fully mixing the various raw materials to obtain the intermediate wax water.
[0153] The surface wax water comprises the following raw materials in parts by weight:
[0154] Silicon source: TEOS 5 parts
[0155] Silicone: MTEOS 10 parts
[0156] Ethanol: 70 parts
[0157] Water: 5 parts
[0158] Acetic acid: 0.02 parts
[0159] Pore former: 1 part of F127.
[0160] The preparation method of the surface coating wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the surface coating wax water, and fully mixing the various raw materials to obtain the surface coating wax water.
[0161] Example 5
[0162] A wax water composition, comprising a base coating wax water, an intermediate wax water, and a surface coating wax water;
[0163] The base coating wax water comprises the following raw materials in parts by weight:
[0164] Water: 85 parts
[0165] Nano-silicon dioxide dispersion: 19 parts
[0166] The nano silicon dioxide dispersion comprises the following raw materials in parts by weight:
[0167] White carbon black: 2 parts of R106, 2 parts of R380;
[0168] Ethanol: 15 parts;
[0169] The preparation method of the primer wax water comprises preparing materials according to the weight composition of each raw material in the primer wax water, and fully mixing each raw material to obtain the primer wax water;
[0170] The intermediate wax water comprises the following raw materials in parts by weight:
[0171] Solvent: 60 parts of dimethyl nylonate;
[0172] Silicone resin: SJ909N 11 parts, SJ909P 11 parts, SJ509P 11 parts, S0234 11 parts;
[0173] Silane coupling agent: 1 part of KH-560, 1 part of KH550, 1 part of KH792;
[0174] Curing agent: 5 parts of N-aminoethylpiperazine, 5 parts of DETA, 5 parts of diaminodiphenylmethane;
[0175] Catalyst: 0.2 parts of dibutyltin dilaurate, 0.2 parts of dibutyltin diacetate, 0.2 parts of tetrabutyl titanate;
[0176] The preparation method of the intermediate wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the intermediate wax water, and fully mixing the various raw materials to obtain the intermediate wax water.
[0177] The surface wax water comprises the following raw materials in parts by weight:
[0178] Silicon source: 6 parts of TEOS, 6 parts of tetramethoxysilane;
[0179] Silicone: 4 parts of octyltriethoxysilane, 4 parts of MTEOS;
[0180] Ethanol: 80 parts
[0181] Water: 2 parts
[0182] Acetic acid: 0.1 parts
[0183] Pore former: F127 0.8 parts.
[0184] The preparation method of the surface coating wax water comprises the following steps: preparing materials according to the weight proportions of various raw materials in the surface coating wax water, and fully mixing the various raw materials to obtain the surface coating wax water.
[0185] Example 6
[0186] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a base coating, an intermediate layer and a top coating sequentially coated on the semi-finished ceramic tile;
[0187] The base coating wax water for forming the base coating layer is from Example 1;
[0188] The intermediate wax water forming the intermediate layer is from Example 1;
[0189] The top coating wax water forming the top coating layer is from Example 1;
[0190] The method for preparing the matte anti-slip, anti-fouling and easy-to-clean marble tile comprises the following steps:
[0191] S4. Use a super-cleaning machine to process semi-finished ceramic tiles with a gloss of 10-12° for the first time. The super-cleaning machine is set to use 12 sets of hard fiber grinding heads + 8 sets of sponge grinding heads for super-bright processing;
[0192] Adding primer wax water dropwise, and coating the primer wax water on the surface of the ceramic tile to obtain a semi-finished ceramic tile with a primer coating;
[0193] S5. Use a super-cleaning machine to process the semi-finished ceramic tiles with a primer layer for a second super-cleaning process. The super-cleaning machine is set to 10 groups of sponge grinding heads for super-bright processing; dripping intermediate wax water, the intermediate wax water is applied to the primer layer of the tile, and the semi-finished ceramic tiles with an intermediate layer are formed;
[0194] S6. Apply the top coating wax water to the bottom coating of the semi-finished ceramic tile with the middle layer, and anneal at 400° C. for 15 minutes to obtain a matte anti-slip, anti-fouling and easy-to-clean ceramic tile.
[0195] Example 7
[0196] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a base coating, an intermediate layer and a top coating sequentially coated on the semi-finished ceramic tile;
[0197] The base coating wax water forming the base coating layer is from Example 2;
[0198] The intermediate wax water forming the intermediate layer is from Example 2;
[0199] The top coating wax water forming the top coating is from Example 2;
[0200] The preparation method is consistent with Example 6.
[0201] Example 8
[0202] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a base coating, an intermediate layer and a top coating sequentially coated on the semi-finished ceramic tile;
[0203] The base coating wax water forming the base coating layer is from Example 3;
[0204] The intermediate wax water forming the intermediate layer comes from Example 3;
[0205] The top coating wax water forming the top coating is from Example 3;
[0206] The preparation method is consistent with Example 6.
[0207] Example 9
[0208] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a base coating, an intermediate layer and a top coating sequentially coated on the semi-finished ceramic tile;
[0209] The base coating wax water forming the base coating is from Example 4
[0210] The intermediate wax water forming the intermediate layer is from Example 4
[0211] The top coating wax water forming the top coating is from Example 4
[0212] The preparation method is consistent with Example 6.
[0213] Example 10
[0214] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a base coating, an intermediate layer and a top coating sequentially coated on the semi-finished ceramic tile;
[0215] The base coating wax water forming the base coating layer is from Example 5;
[0216] The intermediate wax water forming the intermediate layer comes from Example 5;
[0217] The top coating wax water forming the top coating is from Example 5;
[0218] The preparation method is consistent with Example 6.
[0219] Comparative Example 1
[0220] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and an intermediate layer and a top coating layer sequentially coated on the semi-finished ceramic tile; that is, there is no primer layer;
[0221] The intermediate wax water forming the intermediate layer is from Example 1;
[0222] The top coating wax water forming the top coating layer is from Example 1;
[0223] The preparation method is consistent with Example 6.
[0224] Comparative Example 2
[0225] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a primer layer and a topcoat layer sequentially coated on the semi-finished ceramic tile; that is, there is no intermediate layer;
[0226] The base coating wax water forming the intermediate layer is from Example 1;
[0227] The top coating wax water forming the top coating layer is from Example 1;
[0228] The preparation method is consistent with Example 6.
[0229] Comparative Example 3
[0230] A matte anti-slip, anti-fouling and easy-to-clean marble tile, the marble tile comprising a semi-finished ceramic tile, and a primer layer and an intermediate layer sequentially coated on the semi-finished ceramic tile; that is, there is no topcoat layer;
[0231] The base coating wax water forming the intermediate layer is from Example 1;
[0232] The intermediate wax water forming the intermediate layer is from Example 1;
[0233] The preparation method is consistent with Example 6.
[0234] The semi-finished ceramic tiles with an angle of 10-12° in the embodiments or comparative examples may be obtained from the prior art or from the following preparation process:
[0235] Step 1: Prepare a ceramic tile comprising a brick blank, a bottom glaze layer, a flower glaze layer and a surface glaze layer according to a conventional method to obtain a kiln-out ceramic tile;
[0236] Step 2: According to the conventional method, the ceramic tiles out of the kiln are lightly polished using four processes in sequence: rough polishing (3000 fineness elastic module), fine polishing (5000 fineness elastic module), fine polishing (6000 fineness elastic module), and brush polishing (200 fineness soft fiber) to obtain semi-finished ceramic tiles with a glossiness of 10-12°.
[0237] Performance testing:
[0238] 1. The base wax prepared in Examples 1-5 was tested for adhesion performance, the middle wax toughness (according to the paint film impact resistance test standard: GB / T1732-1993 "Paint film impact resistance determination method"), and the top wax was tested for scattering and hydrophilicity. The relevant results are summarized in the following Table 1:
[0239] Table 1
[0240]
[0241] It can be seen that in Examples 1-5, the surface wax layer has a very high adhesion level, reaching 5B; the surface wax layer also meets the qualified requirements in the toughness test; at the same time, the surface wax layer reaches 19-26° in scattering, and the hydrophilicity is less than 50°.
[0242] 2. The marble ceramic tiles prepared in Examples 6-10 and Comparative Examples 1-3 were tested for performance, and the relevant results are summarized in Table 2 below;
[0243] Among them: stain resistance is tested according to the standard "GB / T3810.14-2016";
[0244] Table 2
[0245]
[0246] from Figure 1 It can be seen that on the ceramic tile of Example 6, the wax water composition is initially applied evenly, with a smooth outline and no obvious peak-valley structure; Figure 2 In the test, the surface roughness of the ceramic tile of Example 6 increases after being stepped on, and its profile changes from smooth to rough. It can be seen that the surface wax layer has certain plasticity and flexibility. As can be seen from Table 2, the ceramic tiles prepared in Examples 6 to 10 can be erased three times in the anti-graffiti test, with a dry static friction coefficient of 0.69-0.70, a stain resistance of level 5, and a glossiness of 15-18°; in the simulated stepping test: the anti-graffiti test can be erased three times after stepping on, and the dry static friction coefficient after stepping on is 0.71-0.73.
[0247] Comparative Example 1, combined Figure 3 It can be seen that when the ceramic tile lacks the filling of the primer, the middle layer cannot fill the position of the larger hornet's nest. The primer has a filling effect on the pores on the brick surface, making the brick surface less likely to absorb dirt and having better flatness. In the anti-graffiti test, the ceramic tile prepared in Comparative Example 1: it slightly absorbed dirt twice, and the third time it obviously absorbed dirt and could not be wiped off. The dry static friction coefficient is 0.69-0.70, the stain resistance reaches level 5, and the gloss is 15-18°; in the simulated trampling test: the anti-graffiti test after trampling has two slight dirt absorptions, and the third time it obviously absorbed dirt and could not be wiped off.
[0248] The ceramic tile prepared in Comparative Example 2, in the anti-graffiti test: can be erased three times, the dry static friction coefficient is 0.69-0.70, the stain resistance reaches level 5, and the gloss is 18-20°; in the simulated trampling test: the anti-graffiti test after trampling can not be erased three times, and the dry static friction coefficient after trampling is reduced to 0.60-0.63. Figure 4 It can be seen that the surface of the ceramic tile obtained by omitting the middle layer of wax water becomes smooth, and the dry static friction coefficient is lower than 0.65, which makes the anti-slip performance worse than that of general matte tiles.
[0249] The ceramic tile prepared in comparative example 3 can be erased three times in the anti-graffiti test, with a dry static friction coefficient of 0.69-0.70, a stain resistance of level 5, and a glossiness of 35-40°; in the simulated trampling test, the anti-graffiti test can be erased three times after trampling, and the dry static friction coefficient after trampling is 0.71-0.73, and it is found that the ceramic tile has a high glossiness. Figure 5 It can be seen that the ceramic tiles obtained by omitting the surface wax water have a glossiness that exceeds the standard of matte tiles.
[0250] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A matte anti-slip, anti-fouling and easy-to-clean marble tile. It is characterized in that It includes a semi-finished ceramic tile, and a base coating, an intermediate layer, and a surface coating sequentially coated on the semi-finished ceramic tile; The base coating wax water for forming the base coating layer comprises the following raw materials in parts by weight: Water: 80-95 parts Nano-silicon dioxide dispersion: 15-20 parts The nano silicon dioxide dispersion comprises the following raw materials in parts by weight: White carbon black: 2-5 parts Ethanol: 13-15 parts; White carbon black is one or more of R106, R380 and R200; The intermediate wax water forming the intermediate layer includes the following raw materials in parts by weight: Solvent: 50-60 parts Silicone resin: 36-45 parts Silane coupling agent: 1-5 parts Curing agent: 12-15 parts Catalyst: 0.1-1 part; The solvent is one or more of ethanol, n-butanol, propylene glycol methyl ether, glycerol, and dimethyl nylonate; The surface coating wax water for forming the surface coating comprises the following raw materials in parts by weight: Silicon source: 5-15 parts Silicone: 5-10 parts Ethanol: 70-90 parts Water: 1-5 parts Acetic acid: 0.02-0.1 parts Pore forming agent: 0.5-1 part; In the surface wax water, the silicon source is one or two of TEOS and tetramethoxysilane; in the surface wax water, the organosilicon is one or two of octyltriethoxysilane and MTEOS.
2. The matte anti-slip, anti-fouling and easy-to-clean marble tile according to claim 1, It is characterized in that In the raw materials of the intermediate wax water, the organic silicone resin is one or both of SJ909P and SJ509P.
3. The matte anti-slip, anti-fouling and easy-to-clean marble tile according to claim 1, It is characterized in that In the raw materials of the intermediate wax water, the silane coupling agent is one or more of KH560, KH550, and KH792.
4. The matte non-slip, anti-fouling and easy-to-clean marble tile according to claim 1, It is characterized in that In the raw materials of the intermediate wax water, the curing agent is one or more of N-aminoethylpiperazine, DETA, diaminodiphenylmethane, methyltributylacetonato oxime silane, and vinyltributylacetonato oxime silane.
5. The matte anti-slip, anti-fouling and easy-to-clean marble tile according to claim 1, It is characterized in that In the raw material of the intermediate wax water, the catalyst is one or more of dibutyltin dilaurate, dibutyltin diacetate, and tetrabutyl titanate.
6. The matte non-slip, anti-fouling and easy-to-clean marble tile according to claim 1, It is characterized in that In the surface wax water, the pore-forming agent is F127.
7. A method for preparing the matte anti-skid, anti-fouling and easy-to-clean marble tile according to any one of claims 1 to 6, It is characterized in that The following steps are involved: S1. Preparation of base wax water: Prepare materials according to the weight composition of each raw material in the base coating wax water, and fully mix the raw materials to obtain the base coating wax water; S2. Preparation of intermediate wax water: Prepare materials according to the weight composition of each raw material in the intermediate wax water, and fully mix each raw material to obtain the base coating wax water; S3. Preparation of surface wax water: Prepare materials according to the weight composition of each raw material in the surface wax water, and fully mix the raw materials to obtain the surface wax water; S4 semi-finished ceramic tiles for the first ultra-clean and bright treatment; dripping the primer wax water, the primer wax water cast on the surface of the ceramic tile, to obtain a semi-finished ceramic tile having a primer coating; S5. The semi-finished ceramic tile having a primer layer is subjected to a second ultra-clean and bright treatment; adding intermediate wax water droplets, the intermediate wax water is applied to the primer layer of the tile to obtain a semi-finished ceramic tile having an intermediate layer; S6. Applying the surface wax water to the middle layer of the semi-finished ceramic tile obtained in step 5, and subjecting it to heat preservation annealing treatment, a matte non-slip, anti-fouling and easy-to-clean ceramic tile is obtained.
8. The method for preparing the matte anti-skid, anti-fouling and easy-to-clean marble tile according to claim 7, It is characterized in that The first super-brightening treatment and the second super-brightening treatment are performed using a super-brightening machine.
